2023
DOI: 10.3389/fnmol.2023.1148219
|View full text |Cite
|
Sign up to set email alerts
|

Denervated mouse CA1 pyramidal neurons express homeostatic synaptic plasticity following entorhinal cortex lesion

Abstract: Structural, functional, and molecular reorganization of denervated neural networks is often observed in neurological conditions. The loss of input is accompanied by homeostatic synaptic adaptations, which can affect the reorganization process. A major challenge of denervation-induced homeostatic plasticity operating in complex neural networks is the specialization of neuronal inputs. It remains unclear whether neurons respond similarly to the loss of distinct inputs. Here, we used in vitro entorhinal cortex le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 100 publications
2
8
0
Order By: Relevance
“…The biological significance of these alterations is yet to be determined. Earlier research has shown denervation-induced spine density changes in CA1, but no significant functional alterations in CA1 neurons post-SCL after 3 days [22]. The transcriptomic analysis in this previous study also revealed higher MMP16 mRNA levels post-SCL [22], a membrane-bound MMP expressed by microglia, potentially involved in synaptic rewiring and hippocampal spine density regulation [22,60,61].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The biological significance of these alterations is yet to be determined. Earlier research has shown denervation-induced spine density changes in CA1, but no significant functional alterations in CA1 neurons post-SCL after 3 days [22]. The transcriptomic analysis in this previous study also revealed higher MMP16 mRNA levels post-SCL [22], a membrane-bound MMP expressed by microglia, potentially involved in synaptic rewiring and hippocampal spine density regulation [22,60,61].…”
Section: Discussionsupporting
confidence: 61%
“…Entorhinohippocampal slice cultures are particularly valuable in this context as they allow for in vitro investigation while preserving the complex cyto-and fiber architecture of the neuroglial network. This makes them an effective experimental model for studying the morphological, molecular, and functional dynamics of glial cells [22,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research showed denervation-induced spine density changes in CA1, but no significant functional alterations in CA1 neurons post-SCL at 3 days [18]. Transcriptomic analysis in this previous study also revealed higher MMP16 mRNA levels post-SCL [18], a membrane-bound MMP expressed by microglia, potentially involved in synaptic rewiring and hippocampal spine density regulation [18,46,47]. Regardless of these considerations, the results of the present study clearly show distinct responses in glial cells following SCL and with GM6001, a broad-spectrum MMP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical pathway transection was performed with a sterile scalpel in mature tissue cultures (≥ 18 days in vitro) as described in [18]. SCL was applied between the CA3 and the CA1 region of the hippocampus, without affecting the perforant path projections to CA3 (Fig.1a).…”
Section: Methodsmentioning
confidence: 99%